Sawit Off Grade Sebagai Bahan Baku Alternatif Pembuatan Biodiesel Melalui Proses Dua Tahap Menggunakan Katalis Zeolit Alam Yang Dimodifikasi - Ayu Naluri; Hari Rionaldo; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Palm off grade is a sort of CPO mill utilization which is not maximized. Palm off grade produced approximately 7-10% of the processing capacity of the plant CPO. Oil-palm off grade has a high free fatty acid contents, so it needs two stage process to produce biodiesel. The purpose of this research is to produce biodiesel with a maximum yield above 90%, determine the effectiveness of biodiesel production using a two-stage process with natural zeolite catalysts and determine the effect of temperature, mole ratio of oil : methanol and the concentration of catalyst to biodiesel yield. In this research, natural zeolite modified using 75% KOH solution. Then, biodiesel production have done in two stage, that was esterification and transesterification with variation of temperature (50°C, 60°C, 70°C), mole ratio of oil : methanol (1: 6, 1: 8, 1:10) and concentration of catalyst (2%-w, 4%-w, 6%-w) in transesterification. The highest yield of biodiesel is 96.99% at temperature 60°C, mole ratio of oil : methanol 1: 8 and concentration catalyst 4%-w. The result showed that the process conditions which influencing the yield of biodiesel is the reaction temperature and catalyst concentration.Keywords: biodiesel, natural zeolite, off grade palm oil, response surface methodology.